Effects of local infiltration of peripheral blood mononuclear cells with phonophoresis on wound healing in dogs - SIVANI, KOSARAJU; JOTHI, N ARUL; BALAGOPALAN, T P; GURUNATHAN, N; UMA, S (The Indian Journal of Animal Sciences, 2023)
A total of six dogs with extensive wounds of 5×5 cm2 size and above were taken with the objective of evaluating the efficacy of autologous peripheral blood mononuclear cells (PBMC) with phonophoresis on wound healing in dogs. Autologous PBMCs were isolated freshly on 0, 7, 14, 21 and 28th day from blood by using density gradient centrifugation. Obtained PBMC was infiltrated around the wounds. Phonophoresis was done using therapeutic ultrasound massage at 0.5 watts/cm2 for 10 min for all the six animals. Clinical evaluation and wound planimetry was performed during post treatment period. Most affected breed was mongrel and main aetiology was automobile accident. The wounds were mostly located on limbs, neck and abdominal region. PBMC was noticed to be compatible to the tissues. No signs of infection were noticed in the wounds after administration of PBMC, rather healthy granulation tissue-formation, increasing values of wound contraction, epithelization and healing were noticed. PBMC-phonophoresis in wound healing of canines in present study was found to be effective in extensive wounds.